Effects of plyometric and directional training on speed and jump performance in elite youth soccer players - Beato, M.; Bianchi, M.; Coratella, G.; Merlini, M.; Drust, B. (The Journal of Strength and Conditioning Research, 2018)
Soccer players perform approximately 1,350 activities (every 4-6 seconds), such as accelerations/decelerations and changes of direction (CODs) during matches. It is well established that COD and plyometric training have a positive impact on fitness parameters in football players. This study analyzed the effect of a complex COD and plyometric protocol (CODJ-G) compared with an isolated COD protocol (COD-G) training on elite football players. A randomized pre-post parallel group trial was used in this study. Twenty-one youth players were enrolled in this study (mean ± SD; age 17 ± 0.8 years, mass 70.1 ± 6.4 kg, and height 177.4 ± 6.2 cm). Players were randomized into 2 different groups: CODJ-G (n = 11) and COD-G (n = 10), training frequency of 2 times a week more than 6 weeks. Sprint 10, 30, and 40 m, long jump, triple hop jump, and 505 COD test were considered. Exercise-induced within-group changes in performance for both CODJ-G and COD-G: long jump (effect size [ES] = 0.32 and ES = 0.26, respectively) and sprint 10 m (ES = -0.51 and ES = -0.22, respectively), after 6 weeks of training. Moreover, CODJ-G reported substantially better results (between-group changes) in long jump test (ES = 0.32). In conclusion, this study showed that short-term protocols (CODJ-G and COD-G) are important and able to give meaningful improvements on power and speed parameters in a specific soccer population. CODJ-G showed a larger effect in sprint and jump parameters compared with COD-G after the training protocol. This study offers important implications for designing COD and jumps training in elite soccer.